The analysis of economic integration among ASEAN-5 with Japan and USA - Ganeisan, Menakha; Rosni, Bakar, Prof. Dr.; Md. Aminul Islam, Prof. Madya Dr. (AENSI Publications, 2013)
Link to publisher's homepage at http://www.aensiweb.com/